Conceptual Modelling in Information Systems Engineering - Krogstie, John; Opdahl, Andreas Lothe; Brinkkemper, Sjaak (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Conceptual modeling has always been one of the cornerstones for information systems engineering as it describes the general knowledge of the system in the so-called conceptual schema. Krogstie, Opdahl and Brinkkemper compiled 20 contributions from renowned researchers covering all aspects of conceptual modeling on the occasion of Arne Sølvberg's 67th birthday. Many friends of this information systems modeling pioneer happily contributed their latest research results from fields like data modeling, goal-oriented modeling, agent-oriented modeling, and process-oriented modeling. Overall, the contributions reflect the most important developments and application areas of conceptual modeling in recent years, and they also pinpoint trends in conceptual modeling for the next decade. This wide selection corresponds to the broad spectrum of Arne's activities and long-term responsibilities with the VLDB Endowment, IFIP, and ERCIM. Arne was presented with this book at CAiSE 2007, when the event which he cofounded in 1989 returned to his hometown of Trondheim.